THE PRACTICES OF PROJECT-BASED LEARNING TECHNIQUE APPLICATION: EXPERIENCE OF DIFFERENT COUNTRIES - A. P. Kazun; L. S. Pastukhova (Образование и наука)
Introduction. In the educational systems of different countries, much experience has been gained regarding the use of project-based learning. This method is an alternative to traditional lecture-based learning: it helps to pull together a theoretical training material with real life; additionally, it changes the roles of pupils and teachers: students become active fully-competent subjects of an educational process, whereas teachers organize, supervise and direct this process, but do not transfer readily available information.The aim of the publication is an analytical review of the cases of application of project-based learning in Finland, France, Australia, China and the USA, which were described in the articles of foreign peer-reviewed journals.Methodology and research methods. The methodological framework of the present research is based on systemic and active approaches. The general scientific methods of comparative analysis, synthesis and generalization were applied. The case study method was chosen as a basic tool of the research.Results. A brief background to the history of the genesis and development of project-based learning is given. The emphasized features of various approaches to project-based learning application are different in their orientation towards the solution of certain tasks, as well as in the possibilities for selecting goals and means for implementing specific projects. The case studies in Finnish universities are worked out for the development of social skills of students; however, students can choose both the goals and tools of project activities by themselves. The industrial project method has gained a wide popularity in France; the method is focused on the market, therefore, the choice of the goals and instruments is made on account of the needs of a particular employer. The experience of some Australian universities shows that the project-based learning is used to develop professional skills; the choice of instruments occurs with an orientation towards the latest technological advances. In China the key objectives of the project-based learning are various social projects (for example, environmental projects) which are declared at the governmental level. A broad range of versions of project-based learning have been practised for more than one decade in the leading United States universities, colleges and schools: social competences of students are formed by the means of this method; there is an introduction of innovative technologies into educational process; partnerships are build between educational organizations and market; comprehensive ecological programs are created; etc. However, at this stage, the project-based learning is singled out for serious criticism; the analysis of previous experience and the search for solutions are conducted in order to increase the efficiency of education and improve academic performance of students.Scientific novelty. In the Russian Pedagogy, this paper is the first attempt for understanding and generalizing the experience of international project-based learning application.Practical significance. The materials of the publication provide a possibility for education administrators and educators-practitioners to get familiarized with the educational potential and a variety of approaches of project-based learning in order to adopt the best and most appropriate methods towards the Russian realias and the Russian educational institutions.